1996
DOI: 10.1097/00007890-199604150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Variables in Organ Donors That Affect the Recovery of Human Islets of Langerhans1

Abstract: In an attempt to reduce the variability in the yields of human islets isolations and to identify donor factors that were potentially deleterious, we retrospectively reviewed 153 human islets isolations in our center over a 3-year period. Isolations were performed using controlled collagenase perfusion via the duct, automated dissociation, and Ficoll purification. Factors leading to successful isolations (recovery of >100,000 islet equivalents at a purity >50%) were analyzed retrospectively using univariate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
240
5
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 294 publications
(262 citation statements)
references
References 19 publications
15
240
5
2
Order By: Relevance
“…Few analyses of islet isolation have been reported [4][5][6][7][8]. Consistent with the multivariate analysis of our data, most of these reports also found that high numbers of islets were best obtained from donors with high BMI [4,5,7,8,17,18].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Few analyses of islet isolation have been reported [4][5][6][7][8]. Consistent with the multivariate analysis of our data, most of these reports also found that high numbers of islets were best obtained from donors with high BMI [4,5,7,8,17,18].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the multivariate analysis of our data, most of these reports also found that high numbers of islets were best obtained from donors with high BMI [4,5,7,8,17,18]. This condition is often considered to be a marker of insulin resistance and of high metabolic demand, both of which represent a stimulus for islet neogenesis (beta cell adaptation) that increases the overall native beta cell mass [19].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There is a clear relationship between these insults and reduced success of subsequent islet isolation (16,17,21,41,42). The improvement in islet yield that results from Pefabloc use during islet isolation suggests that trypsin is directly destructive of islets, and reveals the large role of trypsin-mediated pancreas injury.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreata from M. nemestrina were used to model the effect of immediate TLM preservation with minimally injured pancreata, for which equivalent human organs were not available. However, the human marginal-pancreas experiments are of particular clinical importance, as marginal donors and organs with preservation times in excess of 12 h account for a large percentage of the cadaver pool available for clinical transplantation (21). Unexpectedly, we discovered that the benefits of TLM preservation on marginal human pancreata develop over as long as 24 h or more of storage (Stevens, in preparation).…”
Section: Introductionmentioning
confidence: 99%